Analisis Kepuasan Penggunaan Layanan Telemedicine - Muhlizardy Muhlizardy; Ilham Karin Rizkiawan; Nannyk Widyaningrum; Husnaa Dian Puspita; Yunuarti Yunuarti (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Telemedicine, as a form of evolution in the field of health services, has emerged as a response to the challenges and opportunities arising from advances in information and communication technology (ICT). In the era of globalization and digitalization, the concept of telemedicine has revolutionized the way medical services are provided, providing broader, more efficient, and innovative access to healthcare. The purpose of this study was to determine the relationship between service quality and satisfaction among telemedicine users in Surakarta City. This research method is a quantitative descriptive method by distributing online questionnaires (google form). The population in this study are telemedicine users in the Surakarta City area. While determining the number of samples using the Lemeshow formula with a sample of 96 respondents. The results showed that most of the respondents were aged 36-45 years (30.2%), female (51%). The education level of the majority of respondents graduated from high school or equivalent (31.2%). The level of employment of civil servants and self-employed (18.8%) and the activity that is often used is to consult a doctor (66.7%). A total of 3 - 4 times using telemedicine a total of 42.7%. While the results of the description of the quality of services provided are in the good category (72.9%) and the description of satisfaction is in the satisfied category (66.7%). The conclusion in this study is that there is a relationship between service quality and satisfaction with the use of telemedicine services indicating a significant and positive relationship (p value = 0.000).